GAMBARAN PSYCHOLOGICAL WELL-BEING LANJUT USIA DI KELURAHAN LATENG BANYUWANGI TAHUN 2019: Description Of Psychological Well-Being On Elderly In Lateng Village Banyuwangi 2019 - Rifki Rifaldi; Ayik Mandagi (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2019)
Sick on humans not only presented by come to the hospital and drink medicine. Individuals with sick can be screening by disruption of psychological health and increased anxiety. The Unhealthy psychological state signed with old age people feel anxiety more than usual. Feelings of comfort with life can emerge from Psychological well-Being. The main objective of this study was to determine a description of Psychological Well Being in the Elderly. This research is descriptive quantitative research using a cross-sectional study. Research held on 13 May 2019 until 14 May 2019. Population in this research is the elderly in RT IV RW IV Lateng Village and a total people has age 60- â‰¥90 year is 30 people. Saturated sample techniques used in this research. Data was collected using the general wellbeing schedule questionnaire. The data processed through phase cleaning, coding, and then tabulate the data then presented in table form as well as in descriptive. The results showed the elderly have Psychological Well-Being on a good category of 28 respondents (93,3%). The conclusion of this research the level of psychological well being elderly in RT IV RW IV Lateng Village be at a good level. The good PWB well influenced by social support, interaction, activities to prevent the decline of organ function. It is recommended for the elderly to maintain physical activity and communication with their neighbors so that psychological well-being is maintained.